Evaluation of Sexual Risk Behavior Among Study Participants in the TDF2 PrEP Study Among Heterosexual Adults in Botswana. (15th December 2016) - Gust, Deborah A.; Soud, Fatma; Hardnett, Felicia P.; Malotte, Charles K.; Rose, Charles; Kebaabetswe, Poloko; Makgekgenene, Lebogang; Henderson, Faith; Paxton, Lynn; Segolodi, Tebogo; Kilmarx, Peter H.
Abstract : Objective: Among participants of a clinical trial to test the efficacy of tenofovir/emtricitabine in protecting heterosexual men and women living in Botswana from HIV infection, the aim was to determine (1) if sexual risk behavior, specifically condomless sex acts and number of sex partners, changed over time, (2) factors associated with condomless sex acts and number of sex partners, and (3) the effect of participant treatment arm perception on risk behavior to address the possibility of risk compensation. Methods: A longitudinal modeling of rates of risk behaviors was used to determine if the rate of condomless sex acts (#acts/person) and rate of sex partners (#partners/person) changed over time and which factors were associated with behavior change. Results: One thousand two hundred participants were analyzed over 1 year. There was a 25% decrease in the rate of sex partners among participants sexually active in the last 30 days. The rate of reported condomless sex acts was greater for males [rate ratio (RR) = 1.34; confidence interval (CI): 1.07 to 1.67] and participants whose sexual debut in years was ⩽15 years of age (RR = 1.65; CI: 1.14 to 2.38) and 16–17 (RR = 1.68; CI: 1.22 to 2.31) compared with those ≥20 years. Rate of reported sex partners was greater for males (RR = 3.67; CI: 2.86 to 4.71) and participants whose age at sexual debut in years was ⩽15 (RR = 2.92; CI: 2.01 to 4.22) and 16–17 (RR = 2.34; CI: 1.69 to 3.24) compared with those ≥20. There was no effect of participant treatment arm perception on risk behavior. Conclusions: Our study of preexposure prophylaxis to prevent HIV infection found no evidence of risk compensation which may have been due to participants' motivations to reduce their risk behaviors and risk-reduction counseling. Abstract : Supplemental Digital Content is Available in the Text.